Small cell variant of anaplastic large cell lymphoma with positive immunoreactivity for CD99 - Mohd Sidik, Shiran; Tan, Geok Chin; Abdul Rahman, Sabariah; Chye, P. C.; Pathmanathan, Rajadurai (Malaysian Medical Association, 2008)
A 13 year old boy presented with a huge mass on his right arm of 6 months duration. Histopathological examination revealed sheets of malignant small round blue cells with immunopositivity for LCA, CD43, CD45Ro, CD30, EMA, ALK-1 and CD99, and negativity for CD20, TdT, myogenin, myoD1, NSE, bcl-6, bcl-2 and CD10. Fluorescent In-Situ Hybridization (FISH) testing excluded the diagnosis of Ewing's sarcoma/ PNET. Pathologists need to be aware of the diagnosis of a small cell variant of ALCL, as well as of the fact that CD99 expression commonly occurs in cases of ALK-positive ALCL, in order to distinguish this entity from Ewing's sarcoma/PNET.